دراسة مقارنة لبعض المتغيرات الكينيتيكية اثناء اداء الارسال القاطع بالوضعين (المتباعد والمتقارب) للقدمين في التنس: Comparative Study Of Some Kinetical Variables During Tennis Slice With closed and open foot stance In Lawn Tennis - Tawfeeq, Ahmed; Khairy, Bilal (Journal of Physical Education, 2018)
The research aimed at comparing some kinematical variables during tennis slice using closed and open stance on a footscan. The subjects were four registered tennis players in Kurdistan. The researchers used the footscan to measure some kinematical variables of the foot during the slice with two different stances; closed and open, to identify the differences between the two positions and which one is the best. The researchers concluded that there are significant differences in maximum force, maximum time, and impulse in favor of the open foot stance. Keywords: kinematical variables, open and closed stance, slice, lawn tennis.